Віршування Василя Слапчука в контексті еволюції його творчості - Чуй, Сергій; Chuy, Sergiy (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто вірші Василя Слапчука за хронологічним порядком виходу поетичних збірок. Предмет дослідження  еволюція віршувальної системи поета. Звернено увагу на метрику, ритміку, строфіку, частково – на риму. Визначено характер і способи взаємодії класичних і некласичних віршів. На класичній поезії відбилося захоплення поета верлібрами, що дало змогу експериментувати й урізноманітнювати класичний вірш. Вплив класичного віршування на некласичні поезії виявився у їхньому поділі на строфи, спорадичній римі, поліметричних композиціях (різні системи віршування в одному вірші).The article is dedicated to the latest collection of Vasyl Slapchuk’s poems. It represents all stages of his creative activity in chronological order. The subject of the study is the evolution of the poet’s versification system. The author pays attention to the metrics, rhythmics, versification and partly to the rhyme. The article shows the character and ways of interacting of classical and non-classical poetry. The author’s interest to free verse is reflected in the character of classical poetry. It helped him to make an experiment and diversify the classical poems. The non-classical verse was influenced by the classical poetry: the division into stanzas, sporadic rhyme, polymetric composition (different systems of versification poetry in one poem).
Vasyl Slapchuk’s system of versification in the context of the evolution of his creative activity
Keywords: система віршування; метр; ритм; стопа; рима; строфа; system of versification; meter; rhythm; foot; rhyme; stanza